LittlEars questionário auditivo: processo de validação de conteúdo da versão em português brasileiro em pais de crianças com deficiência auditiva - Leandro, Fabiane Sousa Marques (2013)
Introduction: The technology brings positive outcomes for children with hearing impairment. However, it is needed viable tools that assess the auditory development of very young children who use individual amplification hearing aids or cochlear implant. Many questionnaires on language development and hearing have been applied to parents as an attempt to learn more about the child's performance. For this reason, the questionnaire LittlEars was developed by Coninx et al. (2003) to assess auditory skills of the population of infants and children with hearing age of up to two years old. Objective: The aim of this study is to contribute to the process of semantic and cultural adaptation of the preliminary version of the LittlEars questionnaire in Portuguese in families of children with hearing loss that have been attended by the hearing care network - SUS. Method: This research was conducted in CeAC (PUC-SP) and the subjects are parents of children with hearing loss up to two years old of hearing that received the AASI‟s in the CeAC-Derdic. The families of the children with hearing loss were instructed about the purpose of the instrument and the way of administrating (interview or questionnaire) was chosen according to the preference of the family. Afterwards, they answered the LittlEars questionnaire and they were also informed that the comments, doubts, suggestions, examples, critics or difficulty presented by them, would be useful to finalize the drafting of the adapted version of the questionnaire. In a second step, a group meeting of experts was held for a brainstorming session that discussed each item and the suggestions presented. Results and Discussion: The study included 32 children, being 25 male and 7 female, and 37 subjects answered the questionnaire; of these subjects, 23 were mothers, 5 were mother and father, 2 were fathers and 2 were grandmothers. Regarding the preference for the administration of the instrument, 4 parents chose to answer the search in a questionnaire format, while 28 in an interview format. Of the respondents, only six had no doubt responding to the questionnaire and 24 had doubts. Of the parents who chose to answer the questionnaire format, just a parent left some comments on some items. By applying the preliminary version of the LittlEars in an interview format, it was noted that parents had difficulty understanding some items, while those who answered the questionnaire format did not report difficulties in reading and interpreting the items. The comments of the families were collected and analyzed and a modified version was proposed. Conclusions: The doubts and suggestions on the items of the questionnaire that were presented by the parents were related to vocabulary, idioms and unknown examples. The results obtained from the questionnaire LittlEars in the group studied had varied depending on the hearing age and the SII, suggesting that the translation is sensitive to measure the auditory skills. The new version of the questionnaire being translated into English for equivalence verification, and to be considered appropriate. Important steps were taken in validating the LittlEars questionnaire in Portuguese. Further studies are required to apply the new version and to have a final validation